Tesla's financial performance and stock price success in 2020 - Babazhanov, Zh.; Suleyeva, M.; Zhumatov, M.; Kenenbay, A.; Syrbayeva, D. (International School of Economics KAZGUU, 2023)
Trend for zero-emission vehicles, meaning electric vehicles are growing year by year. One of the most influential company in this market today is Tesla. However, its rise as a market leader started during year 2020, which became crucial for the whole automotive industry. Electric vehicle market still in progress of further development and such an outstanding performance in that year, raises question on the methods developed and used by Tesla to gain investors’ confidence. This could serve as an example for its competitors, that would change their vision on how electric vehicles should be developed. This subsequently requires more visibility and research. For this reason, purpose of this research is to determine the reasons behind Tesla’s success in regards to its share price during 2020. Based on our hypothesis, we believe that financial performance of Tesla doesn’t justify its stock price and a lot comes from investor confidence. To test the hypothesis, we conducted Year on Year (YoY) analysis, as well as Comparable Company Analysis (CCA). We analyzed data obtained from Tesla’s 10-K form, mainly related to its financial performance, then compared these data to its close competitors to see industry trends. All the relevant news and announcements on decisions made by Tesla were gathered to gain comprehensive view on reasons behind these numbers. The results of this research showed that Tesla was clearly overvalued at the time, but investor confidence was high leading to increased share price. Such confidence was obtained from clear and concise decisions and action undertaken by top management: opening of a new factory in different region, freshly introduced Model Y, leadership of Elon Musk, fast response to environmental challenges like COVID-19 during which they reached record production and deliveries and further inclusion of Tesla in S&P 500 index indicated them as a key player in a market
Keywords: Tesla, electric vehicles, Tesla's financial performance; Elon Musk